(3GdSjQ GdcHjQs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s ((3OeTb GdeMQhSI s)
(3ChdgG (B:s
(3jHOC HHGH GdoeSde jNQL ef OGQ GdMQH heYg eGd s
(3BNQgG (B:s
(3adeG GfJgi Edi cJGH GdTQhW MUd GdNdGU hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde Je s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1014s
Keywords: (3Gdabg GdMfajs